Circular economy approaches in complex projects - Ahola, Tuomas; Martinsuo, Miia (Edward Elgar Publishing, 2025)
Projects for delivering complex systems involve significant use of resources, both during their implementation and possible later upgrades. Current sustainability frameworks offer limited insights for promoting sustainable development in project contexts. This chapter draws on the concept of circular economy (CE), focusing on the reduction of resource use in industrial operations, to map out opportunities for increasing sustainability of complex systems. Key aspects of CE approaches are summarized, and two case vignettes are reported, to reveal how such approaches are used in complex system implementation and upgrade projects. The CE practices identified are strongly oriented towards closing resource loops and address technology and design aspects of the project deliverable, whereas CE practices used for complex system upgrade emphasize slowing resource flows and address the routines and processes of the organization operating the project deliverable.
Research Handbook on Sustainable Project Management